Development and Initial Validation of Mindfulness-Based Pain Reduction (MBPR) in Patients With Chronic Low Back Pain - Mehling WE; Brintz CE; Hartogensis W; Wolf C; Rogers K; Adler SR; Strigo IA; Hecht FM (Journal of Pain Research)
Wolf E Mehling,1,2 Carrie E Brintz,3,4 Wendy Hartogensis,2 Christiane Wolf,5 Kirsten Rogers,2 Shelley R Adler,1,2 Irina A Strigo,6,7 Frederick M Hecht2,8 1Department of Family and Community Medicine, University of California, San Francisco, San Francisco, CA, USA; 2Osher Center for Integrative Health, University of California, San Francisco, San Francisco, CA, USA; 3Department of Anesthesiology, Center for Musculoskeletal Research, Vanderbilt University Medical Center, Nashville, TN, USA; 4Osher Center for Integrative Health, Vanderbilt University Medical Center, Nashville, TN, USA; 5InsightLA, Los Angeles, CA, USA; 6Emotion and Pain Laboratory and VA Advanced Imaging Research Center San Francisco Veterans Affairs Health Care Center, San Francisco, CA, USA; 7Department of Psychiatry, University of California, San Francisco, San Francisco, CA, USA; 8Department of Medicine, University of California, San Francisco, CA, USACorrespondence: Wolf E Mehling, Osher Center for Integrative Health, Department of Family and Community Medicine, 1545 Divisadero St. 4th Floor, San Francisco, CA, 94115, USA, Tel +1 415 353 9506, Email Wolf.Mehling@ucsf.eduPurpose: Mindfulness-Based Stress Reduction (MBSR) has shown efficacy for alleviating chronic low back pain (cLBP) and is included in current treatment guidelines. However, benefits are moderate. We aimed to optimize MBSR for chronic pain by using recent research to develop Mindfulness-Based Pain Reduction (MBPR) and test it in patients with cLBP.Patients and Methods: Phase 1: We modified the MBSR curriculum with theory-driven components and convened focus groups with local and international mindfulness and clinical pain management experts to refine an 8-week MBPR program. Phase 2: We recruited participants with cLBP from Northern California using outreach in newsletters, social media, and other methods to test and iteratively modify the curriculum. MBPR was delivered in a group format by videoconference. The first three groups received MBPR; a fourth group was randomized to MBSR or MBPR to assess randomization feasibility. We assessed feasibility and acceptability by attendance, practice logs, and exit interviews. We assessed changes in patient-reported outcome measures for low back pain trials using a single arm (treatment group only) approach at 2 and 6 months with linear mixed models (primary: pain intensity and interference (PEG) scores).Results: Phase 1: The MBPR curriculum included: 1) mindful interoceptive exposure to pain, 2) pain neuroscience education, and 3) yoga postures specifically for cLBP. Phase 2: we enrolled 58 patients in 4 cohorts; 49 completed post-intervention and 41 completed 6-month follow-up assessments; 29 of the 41 received MBPR. Participants attended a mean of 80% of sessions and 23 of 24 participants accepted randomization in the 4th cohort. Mean PEG scores improved for 20 of 29 MBPR participants in a clinically meaningful way (PEG scores > 30%).Conclusion: MBPR was feasible and acceptable. Two-thirds of MBPR participants experienced clinically meaningful improvements in pain intensity and interference scores. MBPR warrants further investigation through a randomized, controlled trial.Keywords: chronic pain, pain management, interoception, interoceptive exposure, mindfulness, attention